Overview of Hypertension Incidence in People with Diabetes Mellitus in Indonesia - Citra Cahyati Nasution; Zata Ismah (International Archives of Medical Sciences and Public Health, 2021)
Individually, hypertension or DM increases the risk of cardiovascular disease and the risk increases sharply when the two coexist and it cause a premature death. This quantitative descriptive study with a cross- sectional design aims to describe the prevalence and risk factors for participants obtained from the 2018 RISKESDAS secondary data were recruited in this study. The results showed that the prevalence of hypertension in People with Diabetes Mellitus in Indonesia was 37,4%. The majority of People with Diabetes Mellitus in Indonesia who suffer from hypertension are female, aged ? 45 years, have low education, have DM duration in the old category (? 10 years), lack of physical activity, lack of fruit and vegetable consumotion, eat fatty foods < 1 serving/day, having obesity and having mental-emotional disorders.